PREPARASI DAN KARAKTERISASI KATALIS PEROVSKITE (La,Sr)MnO3+)" - Wuryaningsih Sri Rahayu (Jurnal Kimia Terapan Indonesia, 1996)
The LaMnO3 and La0.8Sr0.2MnO3+A perovskites were synthesized base on sol-gel method using metal nitrates in required proportions. In the preparation, ethylene-glycol and water were used as the dissolving agents and comparison was made. The amorph gel was obtained from nitrate mixture solutions heated in a range 60-80°C, either under vacuum conditions in rotary evaporator or under normal pressure (atmospheric). Perovskite crystals were obtained from calcination process of the amorph gel, and the product was further characterized by X-ray Diffraction analyzer, BET method, Scanning Electron Microscopy as well as Thermal analyzer (TG-DTA). With regard to the process and characterizations, the product obtained by using ethylene-glycol as the dissolving agent was relatively better than. the one produced in aqueous condition. A specific surface area of the sample with ethylene-glycol as dissolving agent (26 m2/gr.) was wider than the sample prepared in aqueous solution (16 m2/gr.). The percentage of weight loss during the formation of perovskite powder was 50 %, it consisted of water, nitrogen and organic compounds. From the X-ray Diffraction analysis, the structure of the crystalline perovskite was obtained by calcination process at 600°C was rhombohedric with a = 7.7 A and (X, = 90.39°. Oxidation reaction of Carbon Monoxide, Hydrocarbon and Particulate of Diesel Engine on these Perovskite was very much affected by specific surface area, structure and Mn 4+ ion.